Religious Brahui Poetry of Maulana Abdul Majeed Chautio An Overview - Razzaq, Waheed (sourcecoder, 2023)
The first religious and literary institution that played an outstanding role in the development of the Brahui language and literature was Maktaba-e-Durkhani, founded by Moulana Muhammad Fazil Durkhani. It produced several scholars who, during the colonial period, actively resisted Christian missionaries. Hundreds of students graduated from here and started serving religion and language in their rspective areas. All this happened at a time when the subcontinent was under the control of the British, and the condition of Muslims in the subcontinent was very bad. Maulana Muhammad Fazil Durkhani was the first who founded a seminary and school that paid special attention to religious education as well as the publication of religious books in the Brahui and Balochi languages. Thus, numerous scholars of the Darkhani School of thought have rendered valuable services in this regard, but the position achieved by Maulana Nabo Jan Qalandrani and then his son Maulana Abdul Majeed Choutoi in Brahui literature, especially in poetry, belongs to no other poet. This article sheds light on Moulana Abdul Majeed Choutoi’s Brahui religious poetry in detail.